Friday

March 27, 2015

March 27, 2015

Posted by **Monique** on Saturday, August 8, 2009 at 7:29pm.

f(x) = -(x+3)^2, x is greater than or equal to 3

I know the first thing you do is switch the variables, so it looks like this:

x = -(y+3)^2

Then expand:

x = -y^2-6y-9

And solve for y:

x + 9 = -y^2-6y

I get a little confused after that with y. Help please? Thank you very much!

- Math (repost) -
**Marth**, Saturday, August 8, 2009 at 9:40pmAt the step where you have x = -(y+3)^2, you should take the square root of both sides.

sqrt(x) = -(y+3)

-sqrt(x) = y+3

-sqrt(x) - 3 = y

**Answer this Question**

**Related Questions**

Math - How do find the inverse function for this problem: f(x) = -(x+3)^2, x is ...

Math - Find inverse of f if f(x)= x^2-4x+3, (for x is smaller than and equal to ...

math help1 - Okay I am a little bit confused about one math question can you ...

inverse - find f^-1 (x). (this is asking me to find the inverse) f(x) = -(x-2)^2...

Calculus - What is the inverse function of.... f(x) = x^3 - 1 Whats the easiest ...

math - Could you show me step by step how to find the inverse of this problem: ...

Calculus - F(x) = 1-x and g(x) = 1/x These functions have the property that f = ...

Algebra 2 - Find the inverse of the following function: f(x) = 3x + 12 I don't ...

math - The cost of producing q articles is given by the function C=f(q)=100+2q...

Algebra - Myra uses an inverse variation function to model the data for the ...